The pathogenesis of duodenal gastric metaplasia: the role of local goblet cell transformation. Issue 5 (1st May 2000) - Shaoul, R; Marcon, P; Okada, Y; Cutz, E; Forstner, G
Abstract : BACKGROUND AND AIMS: Gastric metaplasia is frequently seen in biopsies of the duodenal cap, particularly when inflamed or ulcerated. In its initial manifestation small patches of gastric foveolar cells appear near the tip of a villus. These cells contain periodic acid-Schiff (PAS) positive neutral mucins in contrast with the alcian blue (AB) positive acidic mucins within duodenal goblet cells. Previous investigations have suggested that these PAS positive cells originate either in Brunner's gland ducts or at the base of duodenal crypts and migrate in distinct streams to the upper villus. To investigate the origin of gastric metaplasia in superficial patches, we used the PAS/AB stain to distinguish between neutral and acidic mucins and in addition specific antibodies to immunolocalise foveolar cell mucin MUC5AC, the foveolar cell secretory product, gastric trefoil factor (TFF1), the mature goblet cell mucin MUC2, and MUC2 core antigen. RESULTS: Cells in focal patches of gastric metaplasia contained secretory granules of both gastric and goblet cell phenotypes. MUC5AC and TFF1 were present as expected in gastric foveolar cells but in addition, MUC2 core antigen, normally present only in the Golgi of intestinal goblet cells, was expressed in secretory granules. Goblet cells in the vicinity of metaplastic patches also expressed both gastric and intestinal antigens. MUC5AC/MUC2 containing goblet cells were most common near the villus tip but were also seen at the base of crypts. Where crypts and Brunner's gland ducts merged they were always seen on the crypt side of the junction. Goblet cells were the only cells to express gastric antigens in these areas. In advanced metaplastic lesions, dual phenotype goblet cells were less evident and fewer cells expressed intestinal mucin antigens. CONCLUSIONS: We suggest that goblet cells that express both intestinal and gastric antigens may represent local precursors of gastric metaplasia undergoing a transition to foveolar-like cells of mixed phenotype at the site of early metaplastic patches. As metaplasia becomes more widespread, a more pure gastric phenotype emerges. This progression is likely to be controlled by local inflammatory signals.